Mathematical Formulas Application For Elementary School Students Using Framework Codeigniter - Rayhan Aulia (International Journal of Computer, Network Security and Information System, 2020)
Mathematics is one of the many sciences that are utilized in everyday life. Both in general and specifically. By using a basic mathematical formula, here, the author tries to review the formulas that have been studied by students from elementary school through high school. This web-based application uses codeigniter which contains 30 basic mathematical formulas.